Analyse du problème d’évolution élastoplastique en présence d’une loi non associée de contact avec frottement - Fassi, Hichame Fihri; Bousshine, Lahbibe; Saxcé, Gery de; Harif, Abderrahmane El; Kouam, Mohammed (European Journal of Computational Mechanics, 2003)
This work is devoted to the analysis, by numerical simulation, of the elastoplastic behaviour of metals and the unilateral contact with Coulomb’s dry friction. With this objective, we present a solution algorithm for elastoplastic evolution, taking into account the unilateral contact with Coulomb’s dry friction. This algorithm consists in an incremental formulation from temporal elastoplastic and unilateral contact laws. The latter is described by means of the bipotential theory. This allows us to use a variational formulation based on a minimum principle. To avoid the non-differentiability of the bipotential, two procedures are presented: the penalisation and the augmented Lagrangien method with the Uzawa’s algorithm.